2023
DOI: 10.3390/cancers15071974
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint and EMT-Related Molecules in Circulating Tumor Cells (CTCs) from Triple Negative Breast Cancer Patients and Their Clinical Impact

Abstract: Triple negative breast cancer (TNBC) is the most aggressive breast cancer subtype. There are few targeted therapies for these patients, leading to an unmet need for new biomarkers. The present study aimed to investigate the expression of PD-L1, CTLA-4, GLU, and VIM in CTCs of TNBC patients. Ninety-five patients were enrolled in this study: sixty-four TNBC and thirty-one luminal. Of these patients, 60 were in the early stage, while 35 had metastatic disease. Protein expression was identified by immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…Furthermore, morphological characteristics of CTCs described by Adam et al and Park et al were observed in subpopulations of CTCs detected in the present study [33,34]. According to the CTC morphology observed on the (CK/PD-L1/CD45) staining, a second slide from each patient was analyzed for the assessment of CXCR4 and JUNB expression in CTCs, using antibodies against CK, CXCR4, and JUNB (CK/CXCR4/JUNB), as we have previously reported [19,30].…”
Section: Triple Immunofluorescence Analysissupporting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, morphological characteristics of CTCs described by Adam et al and Park et al were observed in subpopulations of CTCs detected in the present study [33,34]. According to the CTC morphology observed on the (CK/PD-L1/CD45) staining, a second slide from each patient was analyzed for the assessment of CXCR4 and JUNB expression in CTCs, using antibodies against CK, CXCR4, and JUNB (CK/CXCR4/JUNB), as we have previously reported [19,30].…”
Section: Triple Immunofluorescence Analysissupporting
confidence: 56%
“…In patients, PD-L1 is expressed in cancer cells and inhibits the cytotoxic effect of CD8+ T cells against them [3,16]. Several studies have shown increased PD-L1 protein expression in CTCs of different cancer types, including prostate cancer, which is potentially related to patient outcomes [15][16][17][18][19]. Furthermore, the evolution of molecular assays for the detection of PD-L1 mRNA expression has shown that the detection of PD-L1 expression in CTCs is practicable and can provide real-time clinical information [20].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common form of malignancy affecting Iraqi women, accounting for one-third of all cancers [ 21 , 22 ]. HER-2-positive breast cancers account for more than twenty percent of cases and have a high rate of disease recurrence and mortality [ 23 ]. Given the increasing incidence of breast cancer and HER-2 mutation, identifying new biomarkers to correlate with therapeutic response is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, cells were mounted on an anti-fade reagent containing 4′,6-diamidino-2-phenylindole (DAPI). Subsequently, samples were examined using VyCAP (VyCAP B.V., Enschede, the Netherlands) ( Roumeliotou et al, 2022 , Vardas et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%